Zur Geschichte der deutschen Sprache New edition. - Scherer, Wilhelm; Jankowsky, Kurt R. (Amsterdam/Philadelphia : John Benjamins Pub. Co., 1995)
Wilhelm Scherer (1841-1886) has gained wide recognition for his extraordinary accomplishments in linguistics as well as in literary studies. His first and most important contribution to the development of linguistic science was his monumental work of 508 pages Zur Geschichte der deutschen Sprache, published in 1868. His stated objective was "to subject all aspects of the Germanic grammar to a new treatment." While such a wording sounds rather modest, the actual implementation in his book, if viewed within the framework of his time, might very appropriately be called revolutionary. He broke with.
ZUR GESCHICHTE DER DEUTSCHEN SPRACHE; Editorial page; Title page; Copyright page; TABLE OF CONTENTS; EDITOR'S FOREWORD; EDITOR'S INTRODUCTION; REFERENCES; ABBREVIATIONS; WORKS REFERRED TO IN SCHERER (1868); INDEX OF BIOGRAPHICAL NAMES; ZUR GESCHICHTE DER DEUTSCHEN SPRACHE.
Description based on print version record.
Keywords: German language -- History; German language -- Periodicals; German literature -- Periodicals; German philology -- Periodicals; Language and languages; FOREIGN LANGUAGE STUDY / German; Electronic books